Determination of interface state density in high-k dielectric-silicon system from conductance-frequency measurements - Gomeniuk, Yu.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Capacitance-voltage (C-V ) and conductance-frequency ( G-ω ) techniques were modified in order to take into account the leakage current flowing through the metal-oxide-semiconductor (MOS) structure. The results of measurements of interface state densities in several high −k dielectric – silicon systems, including transition metal (Hf) and rare-earth metal (Gd, Nd) oxides, ternary compounds (LaLuO₃) and silicate (LaSiOx), are presented. It was shown that the interface state densities can be as low as ( 1.5...2) × 10¹¹ eV⁻¹cm⁻² for Al-HfO₃-Si, Pt-Gd₂O₃-Si and Pt-LaLuO₃-Si systems if the dielectric layer is deposited onto (100) silicon wafer surface. The electrically active states are attributed presumably to silicon dangling bonds at the interface between dielectric and semiconductor